A Qualitative Research on Competency- Based Learning Management System and Its Effectiveness - Gül ÖZÜDOĞRU; Hüseyin ŞİMŞEK (Anı Publishing, 2021)
This research aimed to reveal the effectiveness of the Akhi Competency-Based Training Project (ACBTP, called AYDEP), a distinctive learning management system based on user views. The research was designed as a case study, one of the qualitative research methods. The study group of the study consisted of the first-year pre-service teachers and instructors in the Classroom Education Department of a state university in the fall semester during the 2018-2019 academic year. A semi-structured interview form was used as a data collection tool. The data were analyzed with the content analysis method. The results showed that, in general, the system was used for course planning, assessment-evaluation and communication purposes. While the system facilitated planning, supported communication and was easily accessible, it had some limitations as well. Providing user support throughout the process in such systems can increase effectiveness.